Governo aberto, transparência e governo eletrônico nas câmaras municipais paraibanas: um estudo multicaso - Lacerda, Sérvulu Mário de Paiva (2017)
This dissertation presents a debate about open government, transparency and e-government in the municipal councils Paraibanas. Aiming to understand the current stage of transparency and e-government actions that allow access to information, participation and collaboration of society in political and deliberative processes through virtual portals of the Paraíba municipal legislature. To do so, the research is exploratory-descriptive in nature, with quanti-quali approach, made use of two data collection instruments: Questionnaires (CGU Transparency Brazil Scale Checklist, focusing on transparency, and a cut of the Amorim and Almada (2014) questionnaire, to focus on participation and collaboration and a semi-structured interview. As a result, observed that the management of the municipalities of Paraíba is still at an incipient level in terms of transparency, collaboration and social participation. In addition, it was possible to point out as challenges of the Municipalities to implement open government are: the lack of financial resources, the incipient popular participation, the low degree of knowledge of the great part of the population and the digital and physical infrastructure. Therefore, even with current legislation that encourages access to and dissemination and encouragement of national and international bodies for government actions, in order to promote the participation of citizens in political and deliberative processes, this is not enough to institutionalize the model Proposed by the open government.